A Review on methods using capnogram signals for detecting asthmatic patients (Jurnal Teknologi (Sciences & Engineering), 2013)
In this paper, a review on methods for detecting the asthmatic conditions by using capnogram is presented. This is included an investigation on capnography as a new approach for monitoring asthma and related researches. Finally, in this preliminary study, a new method based on signal processing approach is developed to automatic detection of asthmatic patients. This developed algorithm is expected to cluster different states of asthmatic conditions by using the RBF (Radial Basis Function) network, instantaneously. However, manual analysis of capnogram is time-consuming and led to erroneous due to human factor such as tiredness and lack of expertise. In the future, this developed algorithm is expected to help heathcare professional involved in respiratory care as it would be possible to monitor severity of asthma automatically and instantaneously.